Influence of Gases Dissolved in Water on the Process of Optical Breakdown of Aqueous Solutions of Cu Nanoparticles - Baimler, Ilya V.; Lisitsyn, Andrey B.; Gudkov, Sergey V. (Frontiers in Physics, 2020)
The paper investigates the effect of gases dissolved in water on the processes occurring during the laser breakdown of colloidal solutions of nanoparticles. The dynamics of the dependences of the plasma luminosity and acoustic signals on the concentration of nanoparticles under irradiation of colloids of nanoparticles saturated with air, argon, and molecular hydrogen has been studied. It is shown that irradiation of colloids saturated with molecular hydrogen and argon leads to an increase in the integral luminosity and integral acoustic signals in comparison with the control sample saturated with atmospheric gases, which indicates the obvious presence of the influence of gases dissolved in the liquid on the optical breakdown process. The most intense acoustic signals, as well as the brightest breakdowns, were observed when the colloidal solution was saturated with molecular hydrogen.